The Influence of Halal Lifestyle, Brand Equity, and Product Mix on Purchasing Decisions with Purchase Interest as An Intervening - Dinar Nur Diansyah; Agung Guritno (Journal of Islamic Economics (JoIE), 2024)
Introduction: This research aims to evaluate the influence of Halal Lifestyle, Brand Equity, and Product Mix on Purchasing Decisions, with Purchase Interest as an intervening variable. Research Methods: A quantitative approach was employed, with primary data gathered through questionnaires distributed to 100 customers of Ayam Geprek Sa'i in Ambarawa, selected using simple random sampling. Results: The findings indicate that Halal Lifestyle positively and significantly affects Purchasing Decisions, while Brand Equity and Product Mix have negative and insignificant impacts. Additionally, Halal Lifestyle and Brand Equity both positively and significantly influence Purchase Intention, as does Product Mix. Purchase Interest, in turn, positively and significantly impacts Purchasing Decisions and mediates the effects of Halal Lifestyle, Brand Equity, and Product Mix on Purchasing Decisions. Conclusion: This study provides valuable insights into the factors influencing consumer purchasing behavior in the context of halal products.